An Empirical Study on Operational Risk Measurement of Commercial Banks in China - Wang, Yang (2018)
Operational risk is an ancient risk that has existed since the bank started its business activities, but it has not been included in the bank's risk management system in the form of an independent risk.The frequent occurrence of operational risk loss events has caused considerable losses to financial institutions.Effective measurement of operational risk is a premise for reducing risk loss.In this context, the Basel Committee on Banking Supervision regards operational risk as the focus of bank risk management and puts forward operational risk measurement methods.Therefore, the purpose of this dissertation is to conduct empirical research on the operational risk measurement of commercial banks in China.